1977
DOI: 10.1017/s0022215100084589
|View full text |Cite
|
Sign up to set email alerts
|

Otoadmittance measurements in patients with rheumatoid arthritis

Abstract: Analysis of middle ear function has for many years been accomplished by acoustic impedance measurements and this has proved of great clinical value. The vectors which contribute to impedance are functions of mass, stiffness and resistance of the system and information about these components may be obtained by use of the otoadmittance meter. The shape of the tympanogram may be altered both by pathologies which change the relative magnitude of the vectors and by variation in the probe tone frequency. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 16 publications
0
19
0
3
Order By: Relevance
“…The middle ear admittance can either decrease or increase depending on the type of specific pathological changes in the joints at the time of testing. Abnormal collagen metabolism can lead to a lax middle ear system [Moffat et al, 1977;Ozcan et al, 2002;Rosenberg et al, 1978;Raut et al, 2001], probably due to capsular distortion, with subsequent loss of stability in the normal ligament to joint relationships. Increased laxity of the middle ear system could also occur due to atrophic alteration of the lenticular process of the incus as a result of vasculitis that occurs in rheumatoid arthritis causing ossicular discontinuity [Colletti et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…The middle ear admittance can either decrease or increase depending on the type of specific pathological changes in the joints at the time of testing. Abnormal collagen metabolism can lead to a lax middle ear system [Moffat et al, 1977;Ozcan et al, 2002;Rosenberg et al, 1978;Raut et al, 2001], probably due to capsular distortion, with subsequent loss of stability in the normal ligament to joint relationships. Increased laxity of the middle ear system could also occur due to atrophic alteration of the lenticular process of the incus as a result of vasculitis that occurs in rheumatoid arthritis causing ossicular discontinuity [Colletti et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that there is more SNHL caused by inner ear involvement in patients with RA (24-60%) than in controls (1)(2)(3)(4)(5)(6)(7). Other investigations suggest the synovial involvement of the middle ear joints (1,2,(7)(8)(9)(10)(11)(12)(13) because the incudomalleolar and incudostapedial joints are true diarthroses and may therefore be subject to the same rheumatic lesions as any other articulation in the body. However, the existence of middle ear joint involvement in RA is highly controversial to date.…”
mentioning
confidence: 99%
“…Reiter et al [8] studied middle ear admittance in RA patients and found an increased incidence of both conductive and sensorineural hearing losses. While the incidence of tympanometric patterns for 660 Hz susceptance expressed in the study of Reiter et al (Table 3) tended to support the data of Moffat et al [7] the prevalence of converging tympanometric patterns did not support a loosening phenomenon. 3).…”
Section: Discussionmentioning
confidence: 53%